Creating a cognitive metric of programming task difficulty - de Alwis, Brian; Murphy, Gail C; Minto, Shawn (International Conference on Software Engineering 2008, 2008)
Conducting controlled experiments about programming activities often requires the use of multiple tasks of similar difficulty. In previously reported work about a controlled experiment investigating software exploration tools, we tried to select two change tasks of equivalent difficulty to be performed on a medium-sized code base. Despite careful effort in the selection and confirmation from our pilot subjects finding the two tasks to be of equivalent difficulty, the data from the experiment suggest the subjects found one of the tasks more difficult than the other.